Spatial Hierarchy of Climate Injustice - Ikporukpo, Chris O.; Ikporukpo, Ninane Nina (Advances in Social Sciences Research Journal, 2022)
Background: Climate justice has emerged as an organising frame in the attempt at addressing the challenge of climate change. The principle that there should be no disproportionality in the burden of climate change, which underlies climate justice, is widely accepted. Be that as it may, climate justice analysis is usually based on an assumption that the global climate system is the norm. This article, based on facts and figures, makes the case for a spatial hierarchical organization of climate justice analysis. Methods: Data from four sources are used. These are published researches, position papers by climate change related organizations, statistical bulletins/abstracts of relevant organizations, and field observations/field records. A descriptive approach is the basic information/data analysis method from which conclusions are derived. Results and Discussion: Three spatial tiers of climate change and associated climate injustice (global, regional, and local) are identified, characterized and analyzed. The global one, which is the usual one discussed by extant works, though couched in terms of anthropogenic climate change, has a natural dimension. In contradistinction, the regional and the local ones are purely anthropogenic. The regional component examined is regional transborder pollution and the associated challenge of acid precipitation. Gas flaring in the Niger Delta region of Nigeria and the associated challenges form the basis of the local dimension. Conclusion: Climate (in)justice cannot be analyzed simply from the perspective of the global climate system. A spatial hierarchical organization is possible. Such a framework could be employed in other cases beyond the examples used here.